A Predictive ‘Quality of Use' Model in Blended Learning - Nasirun, Noraini; Noor, Sarina Muhamad; Yusoff, Rushamie Zien; Othman, Abdul Aziz (International Review of Management and Marketing, 2016)
The aim of this study is to develop a predictive model based on ‘quality of use' concept in blended learning using flipped classroom. The model incorporated contemporary variables, namely student engagement and student interaction. Data were obtained using survey method. A total of 281 undergraduate students participated in the study. Data were analyzed using SmartPLS. The finding revealed that the ‘quality of use' model is enhanced by integrating student engagement and student interaction. This model is only applicable for the context on this study, hence, a replication is required in order to confirm the variables used in similar research context. Keywords: Quality of Use, student engagement, entrepreneurship education JEL Classifications: I21, O32, O35